Utility of rabies neutralizing antibody detection in cerebrospinal fluid and serum for ante-mortem diagnosis of human rabies. - Tina Damodar; Reeta S Mani; P V Prathyusha (Public Library of Science (PLoS), 2019)
BACKGROUND:Early ante-mortem laboratory confirmation of human rabies is essential to aid patient management and institute public health measures. Few studies have highlighted the diagnostic value of antibody detection in CSF/serum in rabies, and its utility is usually undermined owing to the late seroconversion and short survival in infected patients. This study was undertaken to examine the ante-mortem diagnostic utility and prognostic value of antibody detection by rapid fluorescent focus inhibition test (RFFIT) in cerebrospinal fluid (CSF)/serum samples received from clinically suspected human rabies cases from January 2015 to December 2017. METHODOLOGY/PRINCIPAL FINDINGS:Samples collected ante-mortem and post-mortem from 130 and 6 patients with clinically suspected rabies respectively, were received in the laboratory during the study period. Ante-mortem laboratory confirmation was achieved in 55/130 (42.3%) cases. Real time PCR for detection of viral nucleic acid performed on saliva, nuchal skin, brain tissue and CSF samples could confirm the diagnosis in 15 (27.2%) of the 55 laboratory confirmed cases. Ante-mortem diagnosis could be achieved by RFFIT (in CSF and/or serum) in 45 (34.6%) of the 130 clinically suspected cases, accounting for 81.8% of the total 55 laboratory confirmed cases. The sensitivity of CSF RFFIT increased with the day of sample collection (post-onset of symptoms) and was found to be 100% after 12 days of illness. Patients who had received prior vaccination had an increased probability of a positive RFFIT and negative PCR result. Patients who were positive by RFFIT alone at initial diagnosis had longer survival (albeit with neurological sequelae) than patients who were positive by PCR alone or both RFFIT and PCR. CONCLUSIONS/SIGNIFICANCE:Detection of antibodies in the CSF/serum is a valuable ante-mortem diagnostic tool in human rabies, especially in patients who survive beyond a week. It was also found to have a limited role as a prognostic marker to predict outcomes in patients.